Nanometer silicon dioxide colloidal solution and preparation method of super-hydrophobic coating of nanometer silicon dioxide colloidal solution
By grafting modifiers on the surface of nano-silica and combining ultrasonic and sand grinding processes to prepare nano-silica colloidal solution, the dispersibility and interfacial adhesion problems of nano-silica in super-hydrophobic coatings are solved, and efficient super-hydrophobic performance and safe and environmentally friendly industrial production are achieved.
Patent Information
- Application Number
- CN202511135237.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-13
- Publication Date
- 2025-10-21
AI Technical Summary
It is difficult to prepare stable nano-silica materials with existing technologies, and their dispersibility in super-hydrophobic coatings and interfacial adhesion with the coating matrix are insufficient.
Nano-silica colloidal solution was prepared by grafting modifiers such as KH570, polyethylene glycol 2000, 1H,1H,2H,2H-perfluorodecyltriethoxysilane and γ-vinyltriethoxysilane on the surface of nano-silica, combined with ultrasonic and sanding processes, and blended with wood paint and sprayed on medium-density fiberboard.
The prepared nano-dioxide colloidal solution has good dispersibility, excellent super-hydrophobicity, safety and environmental protection, and is suitable for industrial production. There is no obvious difference in the appearance of the coating, and the contact angle is greater than 150°, showing excellent hydrophobicity.
Smart Images

Figure CN120818255A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of nanomaterials, and in particular to a nano-silica colloidal solution and a method for preparing a super-hydrophobic coating thereof. Background Art
[0002] Superhydrophobic surfaces have developed rapidly in recent years due to their great potential in applications such as anti-corrosion, antibacterial, waterproofing, self-cleaning and protection of wood substrates. With the rise of domestic new energy, their application prospects in solar cells, photovoltaic panels and other fields have become brighter. Their application in automotive glass, glass curtain walls, optical devices and other fields is also a direction pursued by many researchers.
[0003] Silicon dioxide is an acidic oxide that is widely distributed in quartz, sand and natural minerals, accounting for about 12% of the earth's crust. It is an abundant inorganic material. Due to the regularity of its structure, silicon dioxide has good chemical inertness, high mechanical strength, and good high-temperature resistance. Since silicon dioxide nanoparticles have excellent optical properties and can be prepared by adjusting their particle size to obtain corresponding surface roughness to obtain super-hydrophobic composite materials, it is currently the most widely used inorganic material by researchers.
[0004] However, the preparation of stable nano-silica materials has become the focus of current research. The present invention mainly uses grinding to graft a modifier onto the surface of nano-silica during the process of preparing silica into nano-silica. At the same time, the prepared nano-silica colloidal solution is blended with wood paint and then sprayed on a medium-density fiberboard to obtain a coating with super-hydrophobic function. Summary of the Invention
[0005] Based on this, the present invention provides a nano-silica colloidal solution, which has good dispersion performance, is not easy to agglomerate, has good super-hydrophobicity, is safe, environmentally friendly, and can be industrially produced.
[0006] The present invention is achieved through the following technical solutions.
[0007] A nano-silica colloidal solution, comprising, by weight, 1 part of nano-silica and 1-5 parts of ethanol as a dispersion medium;
[0008] The nano-dioxide colloidal solution is a surface-modified nano-dioxide colloidal solution;
[0009] The nano-silica modifier includes one or more of KH570, polyethylene glycol 2000, 1H,1H,2H,2H-perfluorodecyltriethoxysilane, and γ-vinyltriethoxysilane.
[0010] In one embodiment, the mass ratio of the dispersant to the nano-silica is (0.002-0.01):1.
[0011] In one embodiment, the preparation of the nano-silica colloidal solution includes the following steps: mixing nano-silica, a dispersant and a dispersion medium ethanol, ultrasonicating, the ultrasonication time is 20-60 minutes, and stirring for the first time; wherein the conditions for the first stirring include: a rotation speed of 150r / min-600r / min; a duration of 10min to 60min; then adding the stirred nano-silica slurry to a sand mill for grinding, the grinding speed is 1600r / min-2600r / min, and the grinding time is 1-6h.
[0012] In one embodiment, the mass ratio of the nano-silicon dioxide to the dispersion medium ethanol is 1:(1-5);.
[0013] In one embodiment, the mass ratio of the nano-silica to the dispersant is 1:(0.002-0.01).
[0014] The present invention also provides a use of the nano-silica colloidal solution in a super-hydrophobic wood paint.
[0015] The present invention also provides a super-hydrophobic coating, wherein the components of the wood paint coating include 40 parts of polyurethane, 20 parts of nano-silica colloid, 10 parts of curing agent, 29.6 parts of solvent and 0.4 parts of auxiliary agent.
[0016] The present invention also provides a method for preparing the super-hydrophobic wood paint as described above, comprising the following steps:
[0017] The components of the super-hydrophobic wood paint are evenly mixed, sprayed on a medium-density fiberboard, and cured at room temperature.
[0018] In one embodiment, the mixing process is performed in a natural environment at room temperature.
[0019] Compared with the prior art, the nano silica colloid of the present invention has the following excellent effects:
[0020] The invention makes the nano-dioxide colloidal solution after grinding, modification and dispersion have a small dispersed particle size, is in a colloidal state, has good dispersion stability, has no precipitation when centrifuged at 10000r / min, and has a good dispersion effect with the coating matrix material. There is no precipitation after adding the nano-dioxide colloidal solution, and the appearance of the coating after spraying is no obvious difference from that of the coating without the addition when observed with the naked eye.
[0021] Furthermore, the raw materials required for the nano-silica colloidal solution of the present invention are cheap, non-toxic and safe, and the preparation process can be industrially scaled up for production. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 The nano-silica slurry prepared in Example 5;
[0023] Figure 2a Prepare wood paint pictures for Comparative Example 1;
[0024] Figure 2b This is a picture of the wood paint prepared in Example 5; DETAILED DESCRIPTION
[0025] To facilitate understanding of the present invention, the present invention will be described more fully below with reference to the accompanying drawings. The accompanying drawings illustrate preferred embodiments of the present invention. However, the present invention may be implemented in many different forms and is not limited to the embodiments described herein. Rather, these embodiments are provided to provide a more thorough and comprehensive understanding of the present disclosure.
[0026] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, a feature defined as "first" or "second" may explicitly or implicitly include at least one of the features. In the description of the invention, the meaning of "plurality" is at least two, such as two, three, etc., unless otherwise clearly and specifically defined. In the description of the present invention, the meaning of "several" is at least one, such as one, two, etc., unless otherwise clearly and specifically defined.
[0027] The terms "preferably," "more preferably," and the like, used herein refer to embodiments of the present invention that may provide certain benefits under certain circumstances. However, other embodiments may also be preferred under the same or other circumstances. Furthermore, the recitation of one or more preferred embodiments does not imply that other embodiments are not useful, nor is it intended to exclude other embodiments from the scope of the present invention.
[0028] When a numerical range is disclosed herein, the range is considered continuous and includes the minimum and maximum values of the range, as well as every value between such minimum and maximum values. Further, when a range refers to an integer, every integer between the minimum and maximum values of the range is included. In addition, when multiple ranges are provided to describe a feature or characteristic, the ranges can be combined. In other words, unless otherwise indicated, all ranges disclosed herein are understood to include any and all subranges subsumed therein.
[0029] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by those skilled in the art to which the present invention pertains. The terms used herein in the specification of the present invention are for the purpose of describing specific embodiments only and are not intended to limit the present invention. The term "and / or" as used herein includes any and all combinations of one or more of the associated listed items.
[0030] The present invention provides a preparation method for a nanometer silica colloidal solution, wherein the components thereof include, by weight, 1 part of nanometer silica, 1 part to 5 parts of ethanol and (0.002 to 0.01) of a dispersant;
[0031] The dispersant is made of safe and non-toxic raw materials and can be used as a modifier, suspending agent, dispersant, interface adhesive, etc. in nano-dioxide colloids. It has the advantages of being non-toxic and highly stable.
[0032] In a specific example, the nano-silica is commercially available common nano-silica. More specifically, the nano-silica is hydrated precipitation nano-silica powder.
[0033] In a specific example, the particle size of the nano-silica is 200 nm to 4000 nm.
[0034] It can be understood that in the present invention, the particle size of nano-silica includes but is not limited to 200nm, 300nm, 300nm, 800nm, 1000nm, 1500nm, 2000nm, 2500nm, 3000nm, 3500nm, and 4000nm.
[0035] In a preferred example, the purity of the nano-silicon dioxide is 99.6%.
[0036] In a preferred example, the dispersants are all commercially available, and the dispersion medium ethanol is commercially available analytical grade.
[0037] In a specific example, the mass ratio of the dispersant to the nano-silica is (0.002-0.01):1.
[0038] It can be understood that in the present invention, the mass ratio of dispersant to nano-silica includes but is not limited to 0.002:1, 0.004:1, 0.006:1, 0.008:1, and 0.01:1.
[0039] The inventors grafted one or more of the modifiers selected in the invention onto nano-silica, thereby improving the dispersibility of nano-silica in ethanol. The prepared colloid has a uniform and transparent appearance, and the prepared wood paint has excellent super-hydrophobic properties.
[0040] In a specific example, the purity of the nano-silicon dioxide is 99.6% and it is in a powder state.
[0041] More specifically, the particle size of the silicon dioxide is 200 nm to 4000 nm. It is understood that in the present invention, the particle size of nano-silicon dioxide includes but is not limited to 200 nm, 300 nm, 300 nm, 800 nm, 1000 nm, 1500 nm, 2000 nm, 2500 nm, 3000 nm, 3500 nm, and 4000 nm.
[0042] In a specific example, the dispersion medium is analytically pure, and the dispersant is a commercially available product.
[0043] In a specific example, the mass ratio of the dispersant to the nano-silica is (0.002-0.01):1.
[0044] It is understood that in the present invention, the mass ratio of the dispersant to the nano-silica includes but is not limited to 0.002:1, 0.004:1, 0.006:1, 0.008:1, and 0.01:1. Preferably, the mass ratio of the dispersant to the nano-silica is (0.006-0.01):1.
[0045] In a specific example, the preparation of modified nano-silica colloidal solution includes the following steps: ultrasonically mixing nano-silica, dispersant and dispersion medium for 20-60 minutes, and stirring; wherein the stirring conditions include: a rotation speed of 1500r / min-600r / min; and a duration of 10min to 60min.
[0046] It is understood that in the present invention, the stirring speed includes but is not limited to 150r / min, 200r / min, 250r / min, 300r / min, 350r / min, 400r / min, 450r / min, 500r / min, 550r / min, and 600r / min. Preferably, the stirring speed is 560r / min.
[0047] It is understood that the stirring time in the present invention includes but is not limited to 10 min, 20 min, 30 min, 40 min, 50 min, and 60 min. Preferably, the stirring time is 40 min to 60 min.
[0048] In one specific example, the grinding media used in sand milling is zirconium oxide beads.
[0049] In a specific example, the particle size of the zirconia beads used in sand milling is 0.1 mm to 0.8 mm. It is understood that in the present invention, the particle size of the zirconia beads used in sand milling includes, but is not limited to, 0.1 mm, 0.2 mm, 0.3 mm, 0.4 mm, 0.5 mm, 0.6 mm, 0.7 mm, and 0.8 mm. Preferably, the particle size of the zirconia beads used in sand milling is 0.1 mm to 0.2 mm.
[0050] In a specific example, the sand mill is a horizontal sand mill, and after the sand milling is completed, the nano-silicon dioxide slurry is filtered out.
[0051] In a specific example, the mass ratio of nano-silica to the dispersion medium is 1:(1-5).
[0052] It can be understood that in the present invention, the mass ratio of the dispersion medium to the nano-silica includes but is not limited to 1:1, 1:2, 1:3, 1:4, and 1:5.
[0053] In a specific example, the mass ratio of the grinding media to the nano-silica is (6-35):1.
[0054] It can be understood that in the present invention, the mass ratio of grinding media to nano-silica includes but is not limited to 6:1, 8:1, 10:1, 15:1, 20:1, 25:1, 30:1, and 35:1.
[0055] In a specific example, the dispersion medium is ethanol, which is commercially available in analytical grade.
[0056] In a specific example, the stirring temperature is 20° C.-40° C. It can be understood that in the present invention, the stirring temperature includes but is not limited to 20° C., 25° C., 30° C., 35° C., and 40° C.
[0057] In a specific example, the sanding is performed under normal pressure. The sanding is performed under natural environment.
[0058] In a preferred embodiment, the sand mill is a horizontal sand mill. The modifier is grafted onto the surface of the nano-silica through high-energy sand milling, creating a steric hindrance effect. This effectively overcomes the problem of agglomeration caused by the large specific surface area and high surface energy of the nano-silica particles as they become smaller. Furthermore, the grafted organic matter can effectively reduce the interfacial energy between the coating resin and the powder surface, effectively reducing the interfacial adhesion between the powder and the coating resin, allowing the nano-silica to be better dispersed in the coating resin and migrate during the curing process.
[0059] The present invention also provides an application of the super-hydrophobic wood paint as described above.
[0060] The present invention also provides a super-hydrophobic wood paint coating, wherein the components of the wood paint coating include 40 parts of polyurethane, 20 parts of nano-silicon dioxide colloid, 10 parts of a curing agent, 29.6 parts of a solvent and 0.4 parts of an auxiliary agent.
[0061] The present invention also provides a method for preparing the above-mentioned super-hydrophobic wood paint, comprising the following steps:
[0062] Stir the polyurethane and ethanol according to the above formula ratio, then slowly add the above-mentioned number of nano-silica colloidal solution and a certain number of additives, continue stirring for a certain time, then add the curing agent and stir for a certain time.
[0063] In a specific example, the stirring temperature is 20°C to 40°C.
[0064] In a specific example, the stirring speed is 150-600 r / min.
[0065] In a specific example, after stirring, the following steps are also included: spraying, curing and other processes.
[0066] In a specific example, the coating is cured at room temperature after spraying, and the curing time is 2 to 40 hours.
[0067] The following is a further detailed description of a nano silica colloidal solution and a method for preparing a super hydrophobic wood coating of the present invention in conjunction with specific examples. The raw materials used in the following examples, unless otherwise specified, are all commercially available products.
[0068] Example 1
[0069] This embodiment provides a method for preparing a nano-silica colloidal solution and a super-hydrophobic wood paint coating thereof, as follows:
[0070] Step 1: Prepare nano-silica colloidal solution
[0071] Weigh 300g of commercially available nano-silica, 1kg of ethanol, and 0.6g of modifier KH5700 and add them to a 3L beaker, ultrasonicate for 20min, mechanically stir for 30min, then add the stirred slurry into the material barrel of a sand mill, start with a speed of 1600r / min, grind for 30min, increase the speed to 2200r / min, grind for 4h, and discharge.
[0072] Step 2: Preparation of super-hydrophobic wood coating
[0073] A super-hydrophobic wood paint coating was prepared, wherein the components of the super-hydrophobic wood paint coating included, by weight, 40 parts of polyurethane, 20 parts of nano-silica grinding slurry, 29.6 parts of solvent, 0.4 parts of additives, and 10 parts of curing agent, and the super-hydrophobic wood paint coating was prepared by stirring;
[0074] The superhydrophobic wood paint was sprayed on a medium-density fiberboard, cured, and then dried at room temperature for 24 hours, and the contact angle of the coating was measured.
[0075] Example 2
[0076] This embodiment provides a method for preparing a nano-silica colloidal solution and a super-hydrophobic wood paint coating thereof, as follows:
[0077] Step 1: Prepare nano-silica colloidal solution
[0078] Weigh 300 g of commercially available nano-silica, 1 kg of ethanol, and 1.0 g of modifier polyethylene glycol 2000 into a 3 L beaker, ultrasonicate for 20 min, mechanically stir for 30 min, then add the stirred slurry into the material barrel of a sand mill, start with a speed of 1600 r / min, grind for 30 min, increase the speed to 2400 r / min, grind for 4 h, and discharge.
[0079] Step 2: Preparation of super-hydrophobic wood coating
[0080] A super-hydrophobic wood paint coating was prepared, wherein the components of the super-hydrophobic wood paint coating included, by weight, 40 parts of polyurethane, 20 parts of nano-silica grinding slurry, 29.6 parts of solvent, 0.4 parts of additives, and 10 parts of curing agent, and the super-hydrophobic wood paint coating was prepared by stirring;
[0081] The superhydrophobic wood paint was sprayed on a medium-density fiberboard, cured, and then dried at room temperature for 24 hours, and the contact angle of the coating was measured.
[0082] Example 3
[0083] This embodiment provides a method for preparing a nano-silica colloidal solution and a super-hydrophobic wood paint coating thereof, as follows:
[0084] Step 1: Prepare nano-silica colloidal solution
[0085] Weigh 300 g of commercially available nano-silica, 1 kg of ethanol, and 3.0 g of modifier 1H,1H,2H,2H-perfluorodecyltriethoxysilane and add them to a 3 L beaker, ultrasonicate for 20 min, mechanically stir for 30 min, then add the stirred slurry into the material barrel of a sand mill, start with a speed of 1600 r / min, grind for 30 min, increase the speed to 2000 r / min, grind for 4 h, and discharge.
[0086] Step 2: Preparation of super-hydrophobic wood coating
[0087] A super-hydrophobic wood paint coating was prepared, wherein the components of the super-hydrophobic wood paint coating included, by weight, 40 parts of polyurethane, 20 parts of nano-silica grinding slurry, 29.6 parts of solvent, 0.4 parts of additives, and 10 parts of curing agent, and the super-hydrophobic wood paint coating was prepared by stirring;
[0088] The superhydrophobic wood paint was sprayed on a medium-density fiberboard, cured, and then dried at room temperature for 24 hours, and the contact angle of the coating was measured.
[0089] Example 4
[0090] This embodiment provides a method for preparing a nano-silica colloidal solution and a super-hydrophobic wood paint coating thereof, as follows:
[0091] Step 1: Prepare nano-silica colloidal solution
[0092] Weigh 300 g of commercially available nano-silica, 1 kg of ethanol, and 0.4 g of modifier γ-vinyltriethoxysilane into a 3 L beaker, ultrasonicate for 20 min, mechanically stir for 30 min, then add the stirred slurry into the material barrel of a sand mill, start with a speed of 1600 r / min, grind for 30 min, increase the speed to 2500 r / min, grind for 4 h, and discharge.
[0093] Step 2: Preparation of super-hydrophobic wood coating
[0094] A super-hydrophobic wood paint coating was prepared, wherein the components of the super-hydrophobic wood paint coating included, by weight, 40 parts of polyurethane, 20 parts of nano-silica grinding slurry, 29.6 parts of solvent, 0.4 parts of additives, and 10 parts of curing agent, and the super-hydrophobic wood paint coating was prepared by stirring;
[0095] The superhydrophobic wood paint was sprayed on a medium-density fiberboard, cured, and then dried at room temperature for 24 hours, and the contact angle of the coating was measured.
[0096] Example 5
[0097] This embodiment provides a method for preparing a nano-silica colloidal solution and a super-hydrophobic wood paint coating thereof, as follows:
[0098] Step 1: Prepare nano-silica colloidal solution
[0099] Weigh 300 g of commercially available nano-silica, 1 kg of ethanol, 3.0 g of modifier 1H,1H,2H,2H-perfluorodecyltriethoxysilane, 6 g of polyethylene glycol 20000, and 0.4 g of γ-vinyltriethoxysilane into a 3 L beaker, ultrasonicate for 20 min, mechanically stir for 30 min, then add the stirred slurry into the material barrel of a sand mill, start with a speed of 1600 r / min, grind for 30 min, increase the speed to 2600 r / min, grind for 4 h, and discharge.
[0100] Step 2: Preparation of super-hydrophobic wood coating
[0101] A super-hydrophobic wood paint coating was prepared, wherein the components of the super-hydrophobic wood paint coating included, by weight, 40 parts of polyurethane, 20 parts of nano-silica grinding slurry, 29.6 parts of solvent, 0.4 parts of additives, and 10 parts of curing agent, and the super-hydrophobic wood paint coating was prepared by stirring;
[0102] The superhydrophobic wood paint was sprayed on a medium-density fiberboard, cured, and then dried at room temperature for 24 hours, and the contact angle of the coating was measured.
[0103] Comparative Example 1
[0104] This comparative example provides a method for preparing a nano-silica colloidal solution and a super-hydrophobic wood paint coating thereof, as follows:
[0105] Step 1: Prepare nano-silica solution
[0106] Weigh 300 g of commercially available nano-silica and 1 kg of ethanol into a 3 L beaker, ultrasonicate for 20 min, mechanically stir at a starting speed of 600 r / min, and stop stirring after 3 h before discharging.
[0107] Step 2: Preparation of super-hydrophobic wood coating
[0108] A super-hydrophobic wood paint coating was prepared, wherein the components of the super-hydrophobic wood paint coating included, by weight, 40 parts of polyurethane, 20 parts of nano-silica slurry, 29.6 parts of solvent, 0.4 parts of additive, and 10 parts of curing agent, and the super-hydrophobic wood paint coating was prepared by stirring;
[0109] The superhydrophobic wood paint was sprayed on a medium-density fiberboard, cured, and then dried at room temperature for 24 hours, and the contact angle of the coating was measured.
[0110] Comparative Example 2
[0111] This comparative example provides a preparation method of nano-silica and its super-hydrophobic wood paint, which is as follows:
[0112] Step 1: Prepare nano-silica colloidal solution
[0113] Weigh 300 g of commercially available nano-silica, 1 kg of ethanol, 3.0 g of modifier 1H,1H,2H,2H-perfluorodecyltriethoxysilane, 6 g of polyethylene glycol 20000, and 0.4 g of γ-vinyltriethoxysilane into a 3 L beaker, ultrasonicate for 20 min, mechanically stir at a starting speed of 600 r / min, and stop stirring after 3 h to discharge the material.
[0114] Step 2: Preparation of super-hydrophobic wood coating
[0115] A super-hydrophobic wood paint coating was prepared, wherein the components of the super-hydrophobic wood paint coating included, by weight, 40 parts of polyurethane, 20 parts of nano-silica slurry, 29.6 parts of solvent, 0.4 parts of additive, and 10 parts of curing agent, and the super-hydrophobic wood paint coating was prepared by stirring;
[0116] The superhydrophobic wood paint was sprayed on a medium-density fiberboard, cured, and then dried at room temperature for 24 hours, and the contact angle of the coating was measured.
[0117] The super-hydrophobic effect of the super-hydrophobic wood paint coating prepared by the colloidal solution with better nano-silica slurry obtained in Examples 1-5 and Comparative Examples 1 and 2 was verified after curing.
[0118] like Figure 1 As shown, the slurry after the nano-silicon dioxide dispersion prepared in Example 5 is as follows: Figure 1 It can be seen that through the grinding process, the nano-silica after adding the modifier is in a colloidal state. Since the machine cannot be cleaned very cleanly during the grinding process, there is some pollution, which causes the ground slurry to be black, but the slurry is clear and transparent.
[0119] As shown in Figure 2, (a) is a wood paint spray sample with the addition of nano-dioxide colloids, and (b) is a wood paint spray sample without the addition of nano-dioxide colloids. By comparison, it can be seen that the wood paint with the addition of nano-dioxide colloids and the wood paint without the addition of nano-dioxide colloids are basically the same in appearance and cannot be distinguished by the naked eye. This may be due to the small particle size of the nano-dioxide colloids. At the same time, the addition of silane coupling agent can effectively reduce the interfacial effect between the nano-silica particles and the paint matrix, allowing the nano-silica to be well dispersed in the paint matrix.
[0120] Contact angle test results: The contact angle test can well determine the hydrophobic function of the coating. Generally, a contact angle >90° can be considered that the coating has a hydrophobic function, >130° indicates good hydrophobic performance, and >150° indicates super hydrophobic function.
[0121] Table 1. Contact angle test
[0122] Sample name Contact angle (°) Example 1 86 Example 2 75 Example 3 131 Example 4 94 Example 5 156 Comparative Example 1 67 Comparative Example 2 103
[0123] As can be seen from Table 1, the contact angle of the wood paint coating of Comparative Example 1 without adding any modifier is only 67°, and the coating itself does not have a hydrophobic function, while the wood paint coating of Example 3 with the addition of 1H,1H,2H,2H-perfluorodecyltriethoxysilane has a contact angle of 131°, indicating that the nano-silica material modified with 1H,1H,2H,2H-perfluorodecyltriethoxysilane has a great improvement in the hydrophobicity of the wood paint, while the nano-silica modified with polyethylene glycol 2000 and KH570 does not improve the hydrophobicity of the coating. Clearly, while γ-vinyltriethoxysilane can improve the hydrophobicity of nanosilica after modification, it is not as strong as 1H, 1H, 2H, and 2H-perfluorodecyltriethoxysilane. Therefore, in this experiment, these modifiers were selected to concentrate on modifying nanosilica powder. This effectively improved the dispersion stability of the nanosilica and reduced its interfacial adhesion to the coating matrix, while also significantly enhancing the coating's hydrophobicity. For example, the wood coating prepared in Example 5 exhibited a contact angle of 156°, demonstrating excellent hydrophobicity.
[0124] The technical features of the above-mentioned embodiments can be combined arbitrarily. In order to make the description concise, not all possible combinations of the technical features in the above-mentioned embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0125] The embodiments described above only express several implementation methods of the present invention, which are convenient for understanding the technical solutions of the present invention in a specific and detailed manner, but they cannot be understood as limiting the scope of protection of the invention patent. It should be pointed out that for ordinary technicians in this field, without departing from the concept of the present invention, several variations and improvements can be made, which all fall within the scope of protection of the present invention. It should be understood that the technical solutions obtained by those skilled in the art through logical analysis, reasoning or limited experiments on the basis of the technical solutions provided by the present invention are all within the scope of protection of the claims attached to the present invention. Therefore, the scope of protection of the patent of the present invention shall be based on the content of the attached claims, and the description and drawings can be used to interpret the content of the claims.
Claims
1. A preparation method of a super-hydrophobic nano-silica colloidal material, characterized in that: In parts by weight, the components include 30 parts of nano-silicon dioxide, 69.9 parts of ethanol, and 0.1 parts of a modifier; The modified nano-silica is commercially available ordinary nano-silica; The nanometer silica colloid comprises nanometer silica, dispersion medium ethanol and dispersant.
2. The nano silica colloid according to claim 1, characterized in that The mass ratio of the nano-silicon dioxide to the ethanol is 1:(1-5).
3. The nano silica colloid according to claim 1, characterized in that The preparation of the nano-silica colloid includes the following steps: mixing nano-silica, a dispersant and a dispersion medium, ultrasonicating, and stirring; wherein the ultrasonicating is performed for 20-60 minutes, and the stirring conditions include: a rotation speed of 150 r / min-600 r / min; and a duration of 10 minutes to 60 minutes; then adding the ultrasonicated nano-silica slurry into a sand mill and grinding it at a grinding speed of 1600 r / min-2600 r / min and a grinding time of 1-6 hours.
4. The nano silica colloid according to claim 3, characterized in that The dispersion medium is ethanol.
5. Use of the nano-silica colloid according to any one of claims 1 to 4 in coatings.
6. A super hydrophobic coating, characterized in that, The components include wood paint and the super-hydrophobic coating according to any one of claims 1 to 7 in a mass ratio of (0.05 to 0.5):
1.
7. Super hydrophobic coating according to claim 8, is characterized in that, In parts by weight, the components of the superhydrophobic wood paint coating include 40 parts of polyurethane, 10 parts of curing agent, 29.6 parts of solvent, 20 parts of silica and 0.4 parts of additives.
8. The method for preparing a super hydrophobic coating according to any one of claims 1 to 9, wherein The steps include: The components of the super-hydrophobic coating are mixed, stirred evenly and then sprayed on a medium-density fiberboard (MDF).
9. the preparation method of super hydrophobic coating according to claim 8, is characterized in that, The stirring temperature is room temperature and ventilation is required during the stirring process.